Antoni Marquès, veritable pintor del retaule de la Santíssima Trinitat de la Seu de Manresa (1507) - Altés i Aguiló, Francesc Xavier (Miscel·lània litúrgica catalana, 2008)
The cathedral of Manresa keeps an altarpiece with Catalan late Gothic paintings devoted to the Holy Trinity in the chapel bearing the same name, built between 1480 and 1484. So far it was believed to be the work of an obscure painter named Gabriel Guàrdia, coming from Manresa and hired in 1501. However, new documents show that this altarpiece was in fact ordered in 1506 to Antoni Marquès, a painter set in Barcelona and related to Jaume Huguet?s pupils; he completed it in 1507.